Exploring The Impact Of E-Commerce And Digital Skills On The Consumptive Behavior Of Muslim Generation Z In Banda Aceh - Nanda, Teuku Syifa Fadrizha; Mulia, Rika; Mutiara, Sulis (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2025)
The advancement of digital technology has significantly influenced consumer behavior, particularly among Generation Z, who are closely connected with e-commerce and digital tools. This study aims to analyze the influence of e-commerce and digital skill on the consumptive behavior of Muslim Generation Z in Banda Aceh. A quantitative approach was used through a survey of 100 purposively selected respondents. Data were collected via online questionnaires and analyzed using multiple linear regression. The results show that both e-commerce and digital skill have a positive and significant influence on consumptive behavior, both partially and simultaneously. E-commerce measured by cost efficiency, platform reputation, and transaction ease contribute to impulsive buying behavior. Digital skill including the ability to assess digital information, use social media, and engage in online transactions also increases consumption tendencies, particularly in the absence of ethical awareness. The coefficient of determination (R²) value of 0.637 indicates that 63.7% of the variance in consumptive behavior can be explained by the two variables. These findings are crucial in the context of Muslim communities, where excessive consumption contradicts Islamic values such as tabzir (wastefullness) and israf (extravagance). The study suggests promoting Islamic-based digital literacy to balance technological competence and consumption control.